Harness value-addition in bread wheat (Triticum aestivum) through genotype and location specificity in highly productive north-western Indo-Gangetic plains - MOHAN, D; GUPTA, R K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2005â€“08 to examine the prospect of value-addition in wheat under highly productive environments. A number of processing and nutrition quality attributes were studied in 10 popular bread wheat varieties of the Indo-Gangetic plains at five locations. Significant differences were noticed among varieties, locations and crop seasons. Variety-location interactions were largely insignificant but year Ã— variety registered importance for a number of quality traits. Location effect was not noticed in chapati quality, flour recovery, gluten index and iron content. Bread wheat varieties with acceptable grain quality for the industrial usages were investigated. It was demonstrated that targeting well-characterized production environment and selection of quality superior genotypes are important to augment quality in production supportive wheat areas.